PENULISAN PEREMPUAN DAN BAHASA PEREMPUAN DALAM MENGUNGKAPKAN FENOMENA KEHIDUPAN PADA NOVEL BELENGGU MERAH MUDA KARYA TYAS DAMARIA: KRITIK SASTRA FEMINISME ELAINE SHOWALTER - Aprilia, Arzety; Nensilianti, Nensilianti; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study describes women’s writing and women’s language in the novel Belenggu Merah Muda by Tyas Damaria using Elaine Showalter’s gynocritics approach. This qualitative descriptive research uses textual data from the novel that reflect the female characters’ life experiences. The analysis focuses on three aspects: explicit and implicit sentences, body expressions, and multifocal elements in women’s language. The results show that Damaria portrays women’s experiences through emotional, metaphorical, and reflective language. Explicit sentences reveal the burdens and roles of women, while implicit sentences appear through metaphors that signify the protagonist’s emotional wounds. Body expressions emerge in open, fragmented, and flowing forms, illustrating the character’s psychological conditions. Furthermore, the multifocal aspect reflects women’s layered and complex perspectives on life. These findings affirm that women’s literature serves as a space to articulate women’s experiences authentically